2011
DOI: 10.1111/j.1440-1843.2010.01919.x
|View full text |Cite
|
Sign up to set email alerts
|

The value of computed tomography scanning for the detection of coronary artery disease in patients with idiopathic pulmonary fibrosis

Abstract: Coronary calcification, as assessed by routine CT of the chest, has very good performance characteristics in predicting underlying significant coronary artery disease in patients with IPF. The routine availability of this study enables the ready screening for coronary artery disease in IPF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 18 publications
0
17
0
1
Order By: Relevance
“…In IPF, the prevalence of coronary artery disease (CAD) is high (60%), probably as a consequence of smoking; associated with worse survival; and, importantly, is significant but unrecognised in 20% of cases [91,92]. In this regard, HRCT can be helpful as the presence of moderate-to-severe coronary calcification has a high sensitivity and specificity for the presence of significant CAD, whereas absence of calcification has an extremely high negative predictive value [93].…”
Section: Cardiac Diseasementioning
confidence: 99%
“…In IPF, the prevalence of coronary artery disease (CAD) is high (60%), probably as a consequence of smoking; associated with worse survival; and, importantly, is significant but unrecognised in 20% of cases [91,92]. In this regard, HRCT can be helpful as the presence of moderate-to-severe coronary calcification has a high sensitivity and specificity for the presence of significant CAD, whereas absence of calcification has an extremely high negative predictive value [93].…”
Section: Cardiac Diseasementioning
confidence: 99%
“…This has led to the hypothesis that pulmonary fibrosis promotes atherosclerosis, perhaps through the release of cytokines and growth factors leading to hypercoagulability and chronic inflammation [25,26]. 1); specifically, moderate-to-severe calcification had a sensitivity and specificity of 81 and 85%, respectively, for significant CAD with an associated OR of 25.2 [28]. CAD and other cardiovascular comorbidities such as CHF and stroke accounted for 27% of deaths in one series of IPF patients [4].…”
Section: Coronary Artery Diseasementioning
confidence: 99%
“…In one study, 57 patients with IPF had left heart catheterization that demonstrated significant coronary artery disease in 28%, mild disease in 40% and none in 32%. 75 The median time interval between left heart catheterization and CT was 39 days. The sensitivity and specificity of CT for moderate-to-severe coronary calcification, indicative of significant coronary artery disease, were 81% and 85%, respectively.…”
Section: Imagingmentioning
confidence: 99%